APPLICATION OF ARTS AND CULTURE TO DIGITAL MEDIA TOURISM SECTOR - Adlhan Nury M. Adnan S. A (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The purpose of making this abstract is: To analyze the extent to which art and culture have been applied to the digital media tourism sector. To analyze the strategies and factors that support and inhibit the tourism sector. To describe the efforts that have been made in overcoming the obstacles to the management strategy of digital tourism media. Collection data through observations. Studies that have been carried out using a SWOT analysis show that implementing art and culture in digital media management in the tourism sector in Sumedang district is reasonable and, according to the provisions, not optimal. This is influenced by the presence of several supporting factors (geographic location, regional potential, and societal friendliness) and inhibiting factors (lack of human resource education, lack of supporting facilities and infrastructure, lack of promotion and information, cooperation with private parties, and overlapping. management status).